Gospodarka oparta na wiedzy w regionach Polski na tle europejskiej przestrzeni regionalnej - Strahl, Danuta (Economy Based on Knowledge in Polish Regions at the Background of European Regional Space, 2007)
The article presents research results regarding the European regional space with reference to knowledge based economy. The research analyzed five attributes illustrating economy based on knowledge in 240 regions representing NUTS 2 level. The attributes are as follows: X1 - share of working university graduates in the overall population number aged 26-64, X2 - share of population participating in continual education in the overall population number aged 26-64, X3 - number of patents per 1 million of labour force, X4- share of employees working in services based on knowledge, X5 - share of employees working in high- and midtech industry sectors. The classification of European regional space was carried out having distinguished six groups of regions presenting different levels of knowledge based economy development. The position of Polish regions was defined with reference to values of attributes describing knowledge based economy in the European regional space.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 23-34